2022
DOI: 10.1093/intimm/dxac045
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nucleotide-binding oligomerization domain 2 by muramyl dipeptide negatively regulates Toll-like receptor 9-mediated colonic inflammation through the induction of deubiquitinating enzyme A expression

Abstract: Mutations in nucleotide-binding oligomerization domain 2 (NOD2) are associated with Crohn’s disease (CD). Although NOD2 activation contributes to the maintenance of intestinal homeostasis through the negative regulation of pro-inflammatory cytokine responses mediated by Toll-like receptors (TLRs), the effects of NOD2 activation on interferon (IFN)-α responses induced by TLR9 have been poorly defined. To explore the cross-talk between NOD2 and TLR9, human monocytes or dendritic cells (DCs) were stimulated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(47 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…Several studies have indicated that loss-of-function mutations in nucleotide-binding oligomerization domain 2 (NOD2) have been associated with CD ( 28 ). Of interest, it has been recently indicated, that NOD2 activation in hematopoietic cells protected mice from TLR9-induced exacerbation of DSS-induced colitis by downregulating IFNα responses ( 29 ). Although several immune and non-immune cells may contribute, the exact sources of IFNα in the systemic circulation of CD remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that loss-of-function mutations in nucleotide-binding oligomerization domain 2 (NOD2) have been associated with CD ( 28 ). Of interest, it has been recently indicated, that NOD2 activation in hematopoietic cells protected mice from TLR9-induced exacerbation of DSS-induced colitis by downregulating IFNα responses ( 29 ). Although several immune and non-immune cells may contribute, the exact sources of IFNα in the systemic circulation of CD remain to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Linking our findings with clinical practice, we found that levels of IFNα in serum or/and mRNA expression of selective IFN-signaling-related components in peripheral neutrophils could be surrogate markers of CD activity, positively correlated with the CDAI, a well-established disease severity index which includes endoscopic findings. Recently, colonic tissue biopsies of CD or UC patients with active and remitted disease phases were characterized by the enhanced and reduced expression of IFN-stimulated genes, respectively ( 29 ). Here, we suggest that targeted analysis of peripheral blood neutrophils may be a more specific, easier, and less costly diagnostic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic biopsy samples were obtained during endoscopy and subjected to qPCR as previously described. ( 24 , 34 , 35 ) qPCR analyses were performed using Quantitect primer assays (Qiagen, Valencia, CA). Primers for the target genes were purchased from Qiagen, and SYBR Green-based qPCR was performed using a LightCycler 480 system (Roche, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 200 μL of serum samples were applied to the membrane. Colonic biopsy samples obtained during endoscopy were subjected to quantitative polymerase chain reaction (qPCR) in accordance with our previous report (19)(20)(21)(22). mRNA was isolated from nontumor portions of colonic mucosa from three patients with colon adenoma to determine the mRNA expression in the healthy colonic mucosa.…”
Section: Methodsmentioning
confidence: 99%